Київський горизонт поселення Глеваха - Терпиловський, Р.В. (Археологія, 1999)
До наукового обігу вводяться матеріали нижнього шару поселення Глеваха на Київщині, розташованого на межі київської та черняхівської культур. Сложность историко-культурной ситуации, сложившейся на Киевщине в позднеримское время, состоит в пограничном характере этой территории, находящейся между северной киевской и южной черняховской культурами. Впервые их комплексы в пределах одного памятника удалось достоверно зафиксировать на поселении Глеваха (Васильковский р-н. Киевской обл.). В ходе раскопок первой половины 80-х гг. здесь исследовано 3000 м2 площади. Публикации киевского (нижнего) горизонта поселения и посвящена настоящая статья. К нему принадлежит четыре постройки, 45 ям-погребов, под выносного очага и яма для выжигания угля. Из объектов и культурного слоя происходит лепная керамика киевской культуры и черняховский керамический импорт, пряслица, железные ножи, кресало, долото, бронзовая подвеска-лунница, точильные бруски и др. Хронология горизонта по находкам подвязных фибул и двух роговых гребней определяется в рамках второй половины III — начала IV в. н. э. В начале IV в. в Глевахе фиксируется смена населения, вызванная продвижением черняховско-вельбарских племен. Возможно, эти события в какой-то мере соответствуют войне между венетами и готами Германариха, описанной Иорданом. A complexity of historical and cultural situation in the Kyiv Region in the Later Roman Period derived from the fact that this territory was a border between the northern Kyiv Culture and the southern Cherniakhiv Culture. Archaeological complexes of the both cultures were first reliably investigated in Glevakha settlement (Vasylkiv region, Kyiv oblast). About 3,000 squire m were investigated there in the first half of the 1980s. This paper presents the materials from the Kyiv (the lower) horizon of the settlement. The horizon included four dwellings, 45 storage-pits, the bottom of a fireplace, and the pit for burning out a charcoal. The objects and the horizon itself contained the sherds of handmade vessels attributed to the Kyiv Culture and the imported ceramics of the Chemiakhiv Culture, and also clay spindle, iron knives, strike, chisel, bronze lunnitsa pendant, and whet-stones, etc. The horizon is dated to the period from the second half of the third century to the beginning of the fourth century AD by several fibulas and two horny combs. Because of infiltration of the Cherniakhiv-Wielbark tribes, there were some changes in the composition of the population in the Glevakha settlement at the beginning of the fourth century AD. It seems that these changes were somehow provoked by the war between the Venetes and the Goths of Hermanarich, described by Jordan.